The Role of The Ni/HZSM-5 Ratio on The Anisole Hydrodeoxygenation Reaction - Nugrahaningtyas, Khoirina Dwi; Nurcahyo, I F; Hidayat, Yuniawan; Rahmawati, Fitria; Fadlulloh, Zaki; Heraldy, Eddy; Qurrotul'aini, Nisriina 'Abidah (Molekul, 2024)
ABSTRACT. Bio-oil is a renewable energy source with high oxygen levels, and anisole is a chemical widely employed in research to represent it. Catalytic hydrodeoxygenation (HDO) reduces the oxygen content. A catalyst known as nickel-modified HZSM-5 has shown promising results for HDO. Meanwhile, catalyst efficiency depends on the Ni/HZSM-5 ratio. So, this study aims to determine how the Ni/HZSM-5 ratio influences the catalyst's properties, activity, and selectivity in anisole HDO. The Ni/HZSM-5 catalyst was made using the wet impregnation method with various ratios of Ni/HZSM-5. The catalysts were analyzed for their morphology using scanning electron microscopy-energy-dispersive X-ray (SEM-EDX). The diffraction patterns were studied using X-ray diffraction (XRD). Surface area and porosity were determined through gas sorption analysis (GSA). Then, the acidity strength was evaluated via temperature-programmed ammonia desorption (NH3-TPD). The characterization results show Ni was successfully impregnated and distributed evenly in HZSM-5 without changing the primary structure. Adding Ni metal to HZSM-5 increases the surface area of the catalyst but reduces its acid strength. The catalytic performance of the catalysts was then evaluated in a flow reactor at 400 °C, using 15 mL/min H2 gas. The liquid products of the reaction were analyzed using gas chromatography-mass spectroscopy (GC-MS). The results of the catalytic performance show that Ni4.5/HZSM-5 has the highest catalytic activity in anisole conversion. At the same time, Ni6.4/HZSM-5 shows the highest selectivity towards benzene-toluene-xylene (BTX). Keywords: Hydrodeoxygenation, nickel, anisole, heterogeneous catalyst, acidity.